Enhancing performance of a miniaturized surface plasmon resonance sensor in the reflectance detection mode using a waveguide-coupled bimetallic chip - Lee, Yeon Kyung; Jang, Dae Ho; Lee, Kyeong-Seok; Kim, Won Mok; Sohn, Young-Soo (SPRINGER, 2013)
The characteristics of a waveguide-coupled bimetallic (WcBiM) chip in a miniaturized surface plasmon resonance (SPR) sensor and its detection capability for a low molecular weight biomolecule were investigated. The configuration of the WcBiM chip was gold (Au)/waveguide (ZnS-SiO2)/silver (Ag). In the intensity measurement mode, the sensitivity could be improved by reducing the full width at half maximum (FWHM) of the reflectance curve. The FWHM of the WcBiM chip is narrower than that of the Au chip, which suggests that the slope of the reflectance curve for the WcBiM chip is steeper. In order to generate enhanced resolution, the reflectance should be monitored at the specific angle where the slope is the steepest in the reflectance curve. For the detection of biotin that is a low molecular weight biomolecule, streptavidin was formed on the SPR sensor chip surface. The response of the SPR to biotin at various concentrations was then acquired. The sensitivities of the WcBiM chip and the Au chip were 0.0052%/(ng/ml) and 0.0021%/(ng/ml), respectively. The limit of detection of the biotin concentration for both the WcBiM and Au chips was calculated. The values were 2.87 ng/ml for the WcBiM chip and 16.63 ng/ml for the Au chip. Enhancement of the sensitivity in the intensity detection mode was achieved using the WcBiM chip compared with the Au chip. Therefore, sufficient sensitivity for the detection of a disease-related biomarker is attainable with the WcBiM chip in the intensity measurement mode using a miniaturized SPR sensor.